30 reasons employees hate their managers : what your people may be thinking and what you can do about it - Katcher, Bruce Leslie, 1953- (AMACOM, American Management Association, 2007)
"30 Reasons Employees Hate Their Managers takes your side, but takes your employees' point of view in identifying dozens of things managers do that make employees stop caring, stop producing, and start looking for other jobs. You'll get a firsthand look at many of the surprisingly common "hidden" employee complaints - many of which seem to contradict one another." "This research-based book takes you inside troubled organizations, and shows how management problems translate to poor results. More important, you'll find stories of how such companies overcame and eliminated these dysfunctions. Each chapter also contains a Solutions section offering real, practical strategies for addressing concerns and improving almost any bad situation."